2017
DOI: 10.1038/s41598-017-11756-2
|View full text |Cite
|
Sign up to set email alerts
|

Transient postnatal overfeeding causes liver stress-induced premature senescence in adult mice

Abstract: Unbalanced nutrition early in life is increasingly recognized as an important factor in the development of chronic, non-communicable diseases at adulthood, including metabolic diseases. We aimed to determine whether transient postnatal overfeeding (OF) leads to liver stress-induced premature senescence (SIPS) of hepatocytes in association with liver structure and hepatic function alterations. Litters sizes of male C57BL/6 mice were adjusted to 9 pups (normal feeding, NF) or reduced to 3 pups during the lactati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 72 publications
(66 reference statements)
4
26
0
Order By: Relevance
“…Importantly, these alterations in senescence pathways and Sirt1 expression in the context of transient postnatal overfeeding do not seem to be specific to the kidney. Our group previously showed similar alterations in the liver at adulthood in the same animal model (Yzydorczyk et al, 2017). However, none of the alterations in protein expression described at weaning in the kidney were observed at adulthood.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Importantly, these alterations in senescence pathways and Sirt1 expression in the context of transient postnatal overfeeding do not seem to be specific to the kidney. Our group previously showed similar alterations in the liver at adulthood in the same animal model (Yzydorczyk et al, 2017). However, none of the alterations in protein expression described at weaning in the kidney were observed at adulthood.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, we recently demonstrated that early postnatal overfeeding leads to modifications of senescence pathways and Sirt-1 expression in the liver (Yzydorczyk et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, postnatal overnutrition fol- lowing early intrauterine undernutrition (with/without extrauterine undernutrition) and growth restriction is a particularly deleterious growth pattern for later vascular, renal, and metabolic functions, as observed by our group and others in rats [2,3]. Interestingly, transient postnatal overfeeding during lactation in the absence of any prenatal nutritional alteration leads to hypertension, heart dysfunction, and metabolic disorders in adulthood [35,36]. Calorie restriction at adulthood allows a reversal of heart dysfunction in this model [36].…”
Section: Nutritionmentioning
confidence: 80%
“…At seven months of life, the livers from the NF ( n = 5), OF ( n = 5), NFCR ( n = 5) and OFCR ( n = 5) groups were rapidly removed and fixed in formol as previously described [13]. Equatorial cross-sections were paraffin-embedded and stained with hematoxylin and eosin (H/E) for hepatic structure evaluation and with Masson’s Trichrome to evaluate hepatic fibrosis.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously observed that transient postnatal OF during the suckling period in mice led to liver microsteatosis and fibrosis in adulthood, and this outcome was associated with OS and stress-induced premature senescence (SIPS) [13]. Calorie restriction (CR), as a potential preventive strategy for metabolic disorders, has received considerable interest.…”
Section: Introductionmentioning
confidence: 99%